EMPLOYEE PERFORMANCE AND HUMAN RESOURCE PROTECTION - Ferdinandus Sampe; Pandu Adi Cakranegara; Muhammad Yusuf; Muji Rahayu; Rizki Alfadillah Nasution (SEAN Institute, 2022)
The goal of this study is to look into human resource protection (HR protection) and working conditions at Pt Telkom Indonesia Bandung Branch. This study employed a quantitative approach analysis, including regression method analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing, on a sample of 60 respondents. This study found that protecting human resources and working conditions has a significant positive effect on employee performance.